2006
DOI: 10.1093/brain/awl326
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity in Parkinson's disease during executive processing depends on striatal involvement

Abstract: Patients with idiopathic Parkinson's disease exhibit impairments in executive processes, including planning and set-shifting, even at the early stages of the disease. We have recently developed a new card-sorting task to study the specific role of the caudate nucleus in such executive processes and have shown, using functional magnetic resonance imaging (fMRI) in young healthy adults, that the caudate nucleus is specifically required when a set-shift must be planned. Here the same fMRI protocol was used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
185
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(210 citation statements)
references
References 43 publications
21
185
3
1
Order By: Relevance
“…These findings suggested that both decreased and increased activation can occur in prefrontal areas during cognitive performance, and that the pattern of activity observed in a specific area of the PFC depended on its specific relationship with the striatum for the task at hand. Later, these observation where confirmed in another fMRI study in a similar group of PD patients using a different set-shifting task (that is, MCST) (Monchi et al, 2007) (Figure 8), in which a pattern of cortical activation was characterized by either reduced or increased activation depending on whether the caudate nucleus was involved or not in the task. This activation pattern included not only the prefrontal regions but also posterior cortical areas in the parietal and prestriate cortex.…”
Section: Executive Dysfunction In Pdmentioning
confidence: 57%
See 1 more Smart Citation
“…These findings suggested that both decreased and increased activation can occur in prefrontal areas during cognitive performance, and that the pattern of activity observed in a specific area of the PFC depended on its specific relationship with the striatum for the task at hand. Later, these observation where confirmed in another fMRI study in a similar group of PD patients using a different set-shifting task (that is, MCST) (Monchi et al, 2007) (Figure 8), in which a pattern of cortical activation was characterized by either reduced or increased activation depending on whether the caudate nucleus was involved or not in the task. This activation pattern included not only the prefrontal regions but also posterior cortical areas in the parietal and prestriate cortex.…”
Section: Executive Dysfunction In Pdmentioning
confidence: 57%
“…Indeed, approximately 15-20% of the patients tend to develop severe cognitive impairments, and the risk of developing dementia is two to three times higher in PD patients than in aged-matched controls (Aarsland et al, 1996). The non-motor cognitive and behavioral disabilities include deficits of executive function, language, visuospatial/visuoconstructive abilities, memory, attention, skill learning, as well as behavioral changes such as depression, apathy, and impulse control disorders (Taylor and SaintCyr, 1995;Zgaljardic et al, 2004;Monchi et al, 2004;Owen, 2004;Monchi, 2007;Steeves et al, 2009). Although Roberts et al (1994) have shown that prefrontal DA depletion may cause marked working memory deficits in monkeys, cognitive disabilities in PD have also been associated with DA depletion within the caudate nucleus (Lewis et al, 2003;Carbon et al, 2004;Grahn et al, 2008).…”
Section: Executive Dysfunction In Pdmentioning
confidence: 99%
“…This cognitive apathy might result from brain lesions aff ecting either the lateral (ie, dorsolateral and ventrolateral) prefrontal cortex or the caudate nucleus. 2 Several functional imaging studies 94,95 in patients with Parkinson's disease without dementia have supported this hypothesis, showing that these patients can present with abnormal activation at the level of the dorsolateral or ventrolateral prefrontal cortex and caudate nucleus during executive tasks. Results from glucose metabolism studies [96][97][98] with ¹⁸F-FDG PET in Parkinson's disease have shown that apathy severity is associated with metabolic activity in diff erent cognitive regions, including the inferior medial frontal gyrus, cingulate cortex, insula, cuneus, and tempo roparietal region.…”
Section: Lesions and Neuroimagingmentioning
confidence: 93%
“…Imaging studies demonstrate that these CSTC loops and fronto‐parietal networks are impaired even in early stages of PD before executive impairment at the behavioural level is evident [Monchi et al, 2007; Trujillo et al, 2015]. In early‐stage PD, functional connectivity is impaired in both task‐related and resting‐state networks [Olde Dubbelink et al, 2014, 2013; Stoffers et al, 2008].…”
Section: Introductionmentioning
confidence: 99%